The Message of the 16th Venice Biennale of Architecture 2018 Freespace compared to the message of the other editions - Trammer, Hubert (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
The 16th International Architecture Biennale took place in Venice in 2018 under the title Freespace. Unlike the curators of most editions, its curators abandoned the great narration, but focused attention on the fundamental (daily) values that the architecture could bring. Unfortunately, the reflection of the curators has gone toward a promotional text accompanying investments. The question arises as to how convincing and deep reflection is possible on the fundamental values of architecture.